INTEGRATING ISLAMIC VALUES ON THE MATERIAL OF TOLERANCE AND DIVERSITY IN CIVICS EDUCATION AT NURUL FIKRI ELEMENTARY SCHOOL - Siregar, Nur Jamilah; Salminawati, Salminawati (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aimed to determine the Islamic value of tolerance and diversity in Civic Education at Nurul Fikri Integrated Islamic Elementary School in Sipirok. Data collection techniques using interviews, observation, and documentation. Then, to ensure the validity of the data, it was used through data triangulation. From the results of the study, it was found that the material of tolerance and ethnic diversity is fostered and instilled starting from the elementary school level because then students from an early age can coexist in the life of the nation and state. In addition, the implementation of Civic Education with the integration of Islamic values, such as the relationship between tolerance and Islamic values and prophet stories that tell stories of tolerance, so it can be concluded that the attitude of tolerance and diversity applied at Nurul Fikri Integrated Islamic Elementary School aims to create a school atmosphere that respects each student and does not hesitate to be open both between students and students with teachers and also help each other, help, and cooperate in various activities carried out daily to create a peaceful and prosperous school atmosphere.